Karakter Fisik dan Aktivitas Antibakteri Nanopartikel Perak Hasil Green Synthesis Menggunakan Ekstrak Air Daun Sendok (Plantago major L.) - Dewi, Komang Tri Aksari; Kartini; Sukweenadhi, Johan; Avanti, Christina (Pharmaceutical Sciences and Research, 2019)
Silver nanoparticles have been studied for its application in wound healing therapy, while aqueous extract of Plantago major L has been studied also for its antibacterial and wound healing activity. This study aimed to obtain silver nanoparticles (AgNPs) through a green synthesis pathway using aqueous extract of Plantago major L. The initial study was performed to optimize the three concentration points of Plantago major L. aqueous extract, namely 0.125%, 0.25% and 0.5% and three synthetic temperature points (60 °C, 70 °C, and 80 °C). The formation of AgNPs were confirmed using a UV-Vis spectrophotometer which shows a peak at a wavelength of 445 nm. The obtained silver nanoparticles were then characterized using Dynamic Light Scattering (DLS Nano), Scanning Electron Microscope (SEM) dan X-Ray Diffraction (XRD). The study showed that the extract concentration of 0.25% with an optimum temperature of 70 °C was the optimal combination to produce the best AgNPs, based on the organoleptic parameters (as the color of silver was produced), the highest yield with weight of 9.13 mg and particle size of 129.20 nm with Polydispersity Index (PDI) of 0.25. The morphology of AgNPs showed the spherical shape and the crystallization of AgNPs showed a diffractogram pattern similar to the silver standard using X-Ray Diffraction (XRD). Antibacterial activity of AgNPs was tested against three bacterial strains, namely Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa and was measured with diffusion method using paper disc. The antibacterial activity testing showed that AgNPS has better antibacterial activity than silver nitrate and is equivalent to its comparative antibiotics, gentamicin sulfate for gram-negative bacteria and Chloramphenicol for gram-positive bacteria.